Fundamental host range of Lophodiplosis indentata (Diptera: Cecidomyiidae), the last proposed biological control agent for Melaleuca quinquenervia (Myrtaceae) in Florida. Issue 10 (2nd October 2020) - Smith, Melissa C.; Wright, Susan A.; Brown, Bradley; Purcell, Matthew; Pratt, Paul D.; Clark, Philip; Lollis, James A.
ABSTRACT: Melaleuca quinquenervia (hereafter melaleuca) was until recently one of the worst ecological invaders in Florida. Introduced for horticulture and levee stabilisation during the early twentieth century, melaleuca spread to cover vast areas of the largest freshwater wetlands ecosystem in North America, The Everglades. From 1997 until 2008, four insects and an associated nematode were approved and released for control of melaleuca, three of which are known to have established. Biological control is frequently a slow and incremental process, but with the integration of complimentary control methods (e.g. chemical and mechanical removal), melaleuca infestations are a fraction of their former range. These few persistent infestations are facilitated by conditions that prevent one species, Oxyops vitiosa, the melaleuca snout weevil, from completing its life cycle, which prompted the testing of and application to release Lophodiplosis indentata (Diptera: Cecidomyiidae). This leaf gall forming midge feeds within pea-shaped growths distributed throughout the canopy. No-choice host range tests suggest that L. indentata will occasionally oviposit on unsuitable host plants, but gall induction and formation is only accomplished on M. quinquenervia. A petition for the release of L. indentata was recommended by TAG in May 2020. [word count: 181]